Efektivitas Pembelajaran Berbasis Daring dalam Pandangan Siswa di Dusun Sebero Desa Dalegan Panceng Gresik - Sa’idaturrohmah, Nur; Khofifah, Lailatul (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2022)
The purpose of this study was to conduct learning effectiveness in Sebero hamlet by using online or online. The subjects in the journal are research and the web that discuss online-based learning. The scope of this journal covers school teachers and elementary school children, as well as the role of government in pursuing online learning today. The development of this education is very influential with the success of an information with good communication. And technology that plays a role in today's environment and education is also used for online learning, online learning is useful for information and communication between students connecting with the internet which is usually done forever. This online media uses various research subjects such as WhatsApp, Google Classroom, Edmodo, and other websites. The method we use is to interview several students in Sebero Village.